Altered Serum Iron and Copper Homeostasis Predicts Cognitive Decline in Mild Cognitive Impairment - Mueller, Claudius; Stolte, Jens; Muckenthaler, Martina (Journal of Alzheimer's disease, 2012)
Alzheimer's disease (AD) brain is marked by severe neuronal death which has been partly attributed to increased oxidative stress. The pathophysiology accounting for this free radical injury is not well-delineated at this point, but one hypothesis is